PELATIHAN BAHASA INGGRIS BISNIS BAGI PELAKU WIRAUSAHA MIKRO DI KECAMATAN SEKARBELA, KOTA MATARAM - NTB - Etika Ariyani; Mansurudin, Mansurudin; Miftahul Jannah (Bajang Institute, 2024)
Training Business English for micro entrepreneurs in Sekarbela subdistrict , Mataram city, West Nusa Tenggara Province aims to help micro entrepreneurs promoted their products significantly thus can improve their transactions to countries all over the world effectively . This training held for ten weeks , twice a week with time allocation 90 minutes for each meeting. The participants consists of 18 micro entrepreneurs lived in Sekarbela subdistrict. This training focused on introduction of language functions, grammar and business vocabularies. Participants listened how to read business text correctly, described their products specifically and applied business vocabularies in their daily interaction. They were asked to give examples, suggestions, comments, advices and promotes their product individually. Having active conversation, selling and bargaining their products actively. Method applied in this training were observation, practice and drilling. The result of this training showed that there are improvement among participants communication skills significantly from 12,50 % (befoe treatment) to 61.11% (after treatment) and they tend have more confident performances. The result of this training shown that this training effective to improve micro entrepreneur performance in Sekarbela subdistrict, Mataram – West Nusa Tenggara Province